Historiography, Nation and Racial Changes in Colombia, 1853-1869 - Villegas Vélez, Álvaro Andrés (Pontificia Universidad Javeriana, 2014)
Through an indepth analysis of writings published between 1853 and 1869, this article demonstrates that the writing of history in Colombia was influenced by the modern-colonial experience of learned citizens.  From this perspective, the 19th century writers perceived and described a world in which the racial characters, the singularities of the environment and the local customs, were the basic interpretative tools in order to understand the past modify the present and construct the future. This resulted in a historiography whereby the national territory, the person and the understanding of time, were fractured by the presence of inappropriate alterities.